Information On Workload, Recruitment, Selection and Their Effects on Employee Performance PT. Harvest Engineering Solutions - diena Dwidienawati; Resista Vikaliana (International Journal of Artificial Intelligence Research, 2022)
This paper discusses the effect of the independent variables of workload, recruitment, and selection on the performance of employees of PT. Panen Solusi Engineering either separately or jointly. The method used is the associative linear regression method using a full sample of 85 people. Based on the opinion of previous researchers who stated that recruitment and selection had a positive effect on employee performance. While the workload has a negative effect. By combining these positive and negative influences, it will provide an overview of the effect of workload, recruitment, and selection on the performance of PT. Panen Solusi Engineering. Determination of simple linear regression and multiple linear regression was carried out after testing the validity, reliability, normality, multicollinearity and heteroscedasticity. The significance test for simple regression was carried out by t-test by comparing tcount and ttable. Meanwhile, the significance test for multiple regression was performed using the F-test, by comparing Fcount and Ftable. The results obtained for the effect of workload on the performance of employees of PT. Panen Solusi Engineering is negative and significant because tcount <- ttable.( -10,767<-2,372) Meanwhile, the effect of recruitment and selection partially on the performance of PT. Panen Solusi Engineering is positive and significant because tcount > ttable. (8,670 and 6,451 > 2,372). The effect in percent (%) for workload, recruitment and selection (X2) separately is 58.3%., 47.5%. and 33.4%. Meanwhile, the total influence in % is 62.7%.